Detection and genotyping of human papillomavirus (HPV) in HIV-infected women and its relationship with HPV/HIV co-infection - Badial, Rodolfo Miglioli [UNESP]; DIas, Marina Carrara [UNESP]; Stuqui, Bruna [UNESP]; Melli, Patrícia Pereira Dos Santos; Quintana, Silvana Maria; Bonfim, Caroline Measso Do [UNESP]; Cordeiro, José Antônio; Rabachini, Tatiana; Calmon, Marilia De Freitas [UNESP]; Provazzi, Paola Jocelan Scarin [UNESP]; Rahal, Paula [UNESP] (Wolters Kluwer, 2018)
HPV have been identified as high-risk and low-risk, depending on their association with the development of cancer. HPV infections can be facilitated by co-infection with HIV. Here, we investigated HPV prevalence and genotypes and the risk factors affecting HPV/HIV co-infection. Forty HIV-positive patients had 80 cervical swab samples collected in 2 consecutive years. Polymerase chain reaction and DNA direct sequencing were used to perform HPV genotyping. Statistical analyses were performed regarding risk factors for HPV/HIV co-infection and the occurrence of cervical lesions. HPV DNA was detected in 59 samples (73.75%), and high-risk HPVs were predominant (59.3%). The most prevalent type was HPV56 (17%), followed by HPV16 (15.3%). Patient age did not affect the risk of cervical cancer (P = .84) or HPV prevalence in different years (P = .25/P = .63). CD4 count also did not affect the risk for cervical lesions in the tested samples (P = .15/P = .28). Although the HIV viral load was not correlated with an increase in cervical lesion detection in the first group of analyzed samples (P = .12), it did affect cervical cancer risk in the group of samples analyzed in the following year (P = .045). HIV-infected patients presented a high prevalence of HPV co-infection, and HPV16 and HPV56 were the most prevalent genotypes. Considering this, it is possible that immunodeficiency can contribute to increased susceptibility to HPV56 infection in HIV-infected patients. The association between HIV viral load and the lesions also confirmed the importance of monitoring HIV/HPV co-infected patients with high HIV viral loads.
Keywords: cervical lesions; HIV; HIV co-infection; HPV